The Venezuelan forest law in the framework of sustainable development (Ágora de Heterodoxias, 2017)
The Venezuelan Forest Law (2013) is a regulatory framework for the sustainable management of forests, the country and its people, which takes part of Venezuelan legal instrumentation in accordance with the demands of the national political, social and economic context. The confluence of the multiple environmental, administrative, sanctioning, social, political and economic components contained in the Forest Law in force in Venezuela was analyzed from the commitments for sustainable development exhibited in conventions, agreements and declarations, based on a documentary review, under the systemic perspective, dialectical logic and principle of complementarity present in said Law.  The principles of sustainable development contained in the Constitution of the Bolivarian Republic of Venezuela, Third Generation Rights, Millennium Development Goals, Declaration of Principles for The Sustainable Management of Forests produced in Rio de Janeiro, Program 21 and the Principles for Sustainable Development contained in the Earth Charter, mainstream and constitute the essence of its content.   The Forest Law (2013) regulates forestry activity, from the understanding between the various parties that come together (political, institutional, social, cultural, scientific, ecological, economic, administrative and sanctioning) and their relationship, to give an integral character of sustainable management to the forest reality of the country. However, institutional, legal, economic, ecological and social complementary situations coexist in Venezuela, which delay the purposes of this legal instrument under the principles of endogenous and sustainable development.
Keywords: Forest law; sustainable development; forestry and Venezuela